Exploring Breastfeeding Practices and Influencing Factors Among the KOL Tribe in Uttar Pradesh: A Mixed-Methods Study - Yadav, Surbhi; Ahmad, Shamshad; Lohani, Pallavi; Gahlot, Anju; Kumar, Mahendra (Indian Journal of Community Health, 2024)
Introduction: Breastfeeding is crucial for infant health, yet challenges persist in promoting early initiation and exclusive breastfeeding, particularly among marginalized communities like the KOL tribe in Uttar Pradesh. This study aimed to understand breastfeeding practices among the KOL tribe and identify factors influencing these practices. Methods: A mixed-methods approach was employed, involving quantitative data collection through pre-designed questionnaires and qualitative in-depth interviews with KOL tribe mothers. Sampling included random selection, and data analysis was conducted using SPSS for quantitative data and QDA minor lite software for qualitative data. Results: Socioeconomic challenges were prevalent among the KOL tribe, with most women being illiterate and engaged in manual labour. Breastfeeding practices varied, including delayed initiation, reliance on cow/goat milk, and misconceptions about colostrum Health care utilization was limited, with home deliveries common due to family incompliance. Despite challenges, community support for breastfeeding was reported, and mothers felt comfortable breastfeeding in public. Conclusion: The study underscores the influence of socio-economic factors, cultural beliefs, and limited awareness on breastfeeding practices among the KOL tribe. Targeted interventions focusing on education, community engagement, and improving healthcare access are crucial for promoting optimal breastfeeding practices and improving infant health outcomes in marginalized communities.